A DNA glycosylase from Escherichia coli that releases free urea from a polydeoxyribonucleotide containing fragments of base residues. - Breimer, L (1980)
A poly (dA, [2-14C]dT) copolymer has been synthesized using terminal deoxynucleotidyltransferase. Treatment of the polydeoxyribonucleotide with potassium permanganate converts the thymine residues to urea and N-substituted urea derivatives, while the adenine residues are resistant to oxidation. This damaged polymer has been annealed with an equimolar amount of poly (dT) to generate a double-stranded polydeoxyribonucleotide containing scattered fragmented base residues, which are radioactively labeled selectively. On incubation of the latter with crude cell extracts from E. coli, free urea is released by a DNA glycosylase activity. The enzyme has been partly purified, and appears to be different from previously studied DNA glycosylase. It shows a strong preference for a double-stranded substrate, exhibits no cofactor requirement, and has a molecular weight of 20000 - 25000. Since fragmentation of pyrimidine residues is a major type of base lesion introduced in DNA by exposure to ionizing radiation, it seems likely this DNA glycosylase is active in repair of X-ray-induced lesions.